FACTORS RELATED TO COMPLAINTS OF CONTACT DERMATITIS AMONG MOTORCYCLE MECHANICS IN THE SOUTH AND NORTH KEMBANGAN AREAS, JAKARTA IN 2021 - Maula, Monica Sofia; Rusdy, Mirta Dwi Rahmah; Handayani, Putri; Muda, Cut Alia Keumala (Faculty of Vocational Studies, Universitas Airlangga, 2022)
Background: Occupational contact dermatitis is an inflammation of the skin caused by materials found in the work environment. Purpose: To determine the factors associated with Complaints of Occupational Contact Dermatitis among Motorcycle Workshop Workers in the Kelurahan Kembangan Selatan and Kembangan Utara, Jakarta in 2021. Method: This research is a descriptive-analytic study with a cross-sectional study design. The population of this research is motorcycle repair workers in the southern and northern Kembangan villages amounted 78 workers. The sample in this study amounted to 35 samples of workshop workers with Quota sampling technique. The method of collecting data from the source of information used is in the form of primary data using measuring instruments in the form of questionnaires and observation sheets. Result: The proportion of workers who complained of work-related contact dermatitis were 13 workshop workers (37.1%). Conclusion: Based on the results of statistical tests, it is known that the variable associated with occupational contact dermatitis is the age (p-value 0.004) and working period (p-value 0.005) with complaints of occupational contact dermatitis in motorcycle repair workers in the Kembangan Selatan and Kembangan Utara sub-districts, meanwhile not related between length of contact (p-value 0.282), personal hygiene (p-value 0.689) and the use of PPE (p-value 0.519) with complaints of occupational contact dermatitis in motorcycle repair workers in the Kembangan Selatan and Kembangan Utara areas, Jakarta.